Loss of Protein Phosphatase 1 Regulatory Subunit PPP1R3A Promotes Atrial Fibrillation. Issue 8 (20th August 2019) - Alsina, Katherina M.; Hulsurkar, Mohit; Brandenburg, Sören; Kownatzki-Danger, Daniel; Lenz, Christof; Urlaub, Henning; Abu-Taha, Issam; Kamler, Markus; Chiang, David Y.; Lahiri, Satadru K.; Reynolds, Julia O.; Quick, Ann P.; et al.
Abstract : Background: Abnormal calcium (Ca 2+ ) release from the sarcoplasmic reticulum (SR) contributes to the pathogenesis of atrial fibrillation (AF). Increased phosphorylation of 2 proteins essential for normal SR-Ca 2+ cycling, the type-2 ryanodine receptor (RyR2) and phospholamban (PLN), enhances the susceptibility to AF, but the underlying mechanisms remain unclear. Protein phosphatase 1 (PP1) limits steady-state phosphorylation of both RyR2 and PLN. Proteomic analysis uncovered a novel PP1-regulatory subunit (PPP1R3A [PP1 regulatory subunit type 3A]) in the RyR2 macromolecular channel complex that has been previously shown to mediate PP1 targeting to PLN. We tested the hypothesis that reduced PPP1R3A levels contribute to AF pathogenesis by reducing PP1 binding to both RyR2 and PLN. Methods: Immunoprecipitation, mass spectrometry, and complexome profiling were performed from the atrial tissue of patients with AF and from cardiac lysates of wild-type and Pln -knockout mice. Ppp1r3a -knockout mice were generated by CRISPR-mediated deletion of exons 2 to 3. Ppp1r3a -knockout mice and wild-type littermates were subjected to in vivo programmed electrical stimulation to determine AF susceptibility. Isolated atrial cardiomyocytes were used for Stimulated Emission Depletion superresolution microscopy and confocal Ca 2+ imaging. Results: Proteomics identified the PP1-regulatory subunit PPP1R3A as a novel RyR2-binding partner, and coimmunoprecipitation confirmed PPP1R3A binding to RyR2 and PLN. Complexome profiling and Stimulated Emission Depletion imaging revealed that PLN is present in the PPP1R3A-RyR2 interaction, suggesting the existence of a previously unknown SR nanodomain composed of both RyR2 and PLN/sarco/endoplasmic reticulum calcium ATPase-2a macromolecular complexes. This novel RyR2/PLN/sarco/endoplasmic reticulum calcium ATPase-2a complex was also identified in human atria. Genetic ablation of Ppp1r3a in mice impaired binding of PP1 to both RyR2 and PLN. Reduced PP1 targeting was associated with increased phosphorylation of RyR2 and PLN, aberrant SR-Ca 2+ release in atrial cardiomyocytes, and enhanced susceptibility to pacing-induced AF. Finally, PPP1R3A was progressively downregulated in the atria of patients with paroxysmal and persistent (chronic) AF. Conclusions: PPP1R3A is a novel PP1-regulatory subunit within the RyR2 channel complex. Reduced PPP1R3A levels impair PP1 targeting and increase phosphorylation of both RyR2 and PLN. PPP1R3A deficiency promotes abnormal SR-Ca 2+ release and increases AF susceptibility in mice. Given that PPP1R3A is downregulated in patients with AF, this regulatory subunit may represent a new target for AF therapeutic strategies. Abstract : Supplemental Digital Content is available in the text.